Changes in Land Cover in Temon District Impact of Development of Yogyakarta International Airport - Gafuraningtyas, Dewi; Pradana, Brahim Aji (Jurnal Pertanahan, 2023)
ABSTRACT In recent years, the Indonesian government has built several airports, including the Yogyakarta International Airport (YIA) in the Special Region of Yogyakarta (DIY). With the development of the airport, it will create a multiplier effect in which the growth of various facilities around it to support the needs of airport service users, which were previously very minimal or not even available around the airport area. This condition will certainly impact land cover and use in the surrounding area. This study aims to detect temporal changes in land cover in Temon District before development (2016), after it started operating (2019), and 2022 using several algorithms and indices such as Random Forest, Normalized Difference Built-up Index (NDBI), Normalized Difference Vegetation Index (NDVI), detection via google earth, and nighttime light (NTL). The results show a significant change in land cover, namely an increase in the built-up area while the other land cover classes decrease. Built-up area increased from 246.54 ha (6,72%) in 2016 to 617.83 ha (16,86%) in 2019, primarily due to the construction of airports. By 2022, the built-up area further expanded to 977.25 ha (26,67%), driven by the development of surrounding areas, including settlements, hotels, and other structures. In contrast, other land cover types have shown a decrease in area from 2016 to 2022. For example, vegetated agricultural areas reduced by 515.29 ha, bare land decreased by 111.43 ha, non-agricultural vegetation decreased by 48.81 ha, and water bodies reduced by 55.18 ha. Based on NTL, connectivity from Temon District to the surrounding areas has increased from 2016 to 2022. ABSTRAK Dalam beberapa tahun belakangan ini, pemerintah Indonesia telah membangun sejumlah bandar udara dan salah satunya adalah Yogyakarta International Airport (YIA) di Daerah Istimewa Yogyakarta (DIY). Dengan adanya pembangunan bandara maka akan menimbulkan multiplier effect (efek pengganda), yakni terjadinya pertumbuhan berbagai fasilitas di sekitarnya sebagai penunjang kebutuhan pengguna jasa bandara yang sebelumnya sangat minim atau bahkan belum tersedia di sekitar wilayah bandara. Hal ini tentunya akan memberikan dampak pada tutupan dan penggunaan lahan pada wilayah sekitarnya. Penelitian ini bertujuan untuk mendeteksi adanya perubahan tutupan lahan secara temporal di Kecamatan Temon sebelum pembangunan (2016), saat mulai beroperasi (2019), hingga saat ini (2022) dengan menggunakan beberapa algoritma dan indeks seperti random forest, normalized difference built-up index (NDBI), normalized difference vegetation index (NDVI), deteksi melalui google earth, dan night time light (NTL). Hasilnya menunjukkan bahwa terdapat perubahan yang cukup signifikan pada tutupan lahan, yakni meningkatnya luasan area terbangun sedangkan kelas tutupan lahan lainnya berkurang. Lahan terbangun meningkat dari 246,54 ha (6,72%) pada tahun 2016 menjadi 617,83 ha (16,86%) pada tahun 2019, terutama disebabkan oleh pembangunan bandara. Pada tahun 2022, area terbangun semakin meluas menjadi 977,25 ha (26,67%), didorong oleh pengembangan area sekitarnya, termasuk permukiman, hotel dan lainnya. Sebaliknya, tutupan lahan lainnya menunjukkan penurunan luas dari tahun 2016 hingga 2022. Diantaranya lahan pertanian berkurang 515,29 ha, lahan terbuka berkurang 111.43 ha, vegetasi nonpertanian berkurang 48,81 ha, dan badan air berkurang sebesar 55,18 ha. Berdasarkan NTL, konektivitas dari Kecamatan Temon ke sekitarnya mengalami peningkatan dari tahun 2016 hingga tahun 2022. Berdasarkan NTL, konektivitas dari Kecamatan Temon menuju wilayah sekitarnya semakin meningkat dari periode tahun 2016 hingga 2022.